2004
DOI: 10.1111/j.0953-816x.2004.03455.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of oxytocin neurons in suckled rats: possible role of bilateral innervation of hypothalamic supraoptic nuclei by single medullary neurons

Abstract: We have previously shown that oxytocin neurons located in the four hypothalamic magnocellular nuclei display synchronous bursts of action potentials before each milk ejection. The mechanisms involved in such a synchronization have, however, not yet been elucidated. In this study, we test the hypothesis of an extranuclear synchronization arising from a common extrahypothalamic input innervating bilateral magnocellular nuclei. First, two different retrograde tracers were injected into the right and left supraopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Neurons in this region project both to the SON and PVN. 161 Moos et al 132 however, found that lactating rats suckling bilaterally, but with extensive hypothalamic hemisection, failed to show OT burst synchronization, and the bursting that was observed was dramatically reduced in amplitude compared to controls. This region is near what is commonly referred to as the SON perinuclear zone (PNZ), which also has documented projections to the SON (see Refs.…”
Section: Hypothalamic Circuitrymentioning
confidence: 97%
See 3 more Smart Citations
“…Neurons in this region project both to the SON and PVN. 161 Moos et al 132 however, found that lactating rats suckling bilaterally, but with extensive hypothalamic hemisection, failed to show OT burst synchronization, and the bursting that was observed was dramatically reduced in amplitude compared to controls. This region is near what is commonly referred to as the SON perinuclear zone (PNZ), which also has documented projections to the SON (see Refs.…”
Section: Hypothalamic Circuitrymentioning
confidence: 97%
“…124,125 Synaptic adrenergic (or noradrenergic) profiles making contact with OT neurons have been observed. Li et al 131 found that suckling-induced c-Fos expression was prominent in the A1 and A6 cell groups but not in the NTS, whereas Moos et al 132 reported activation of both A1 and A2 cell groups in the medulla and found numerous noradrenergic neurons could be labeled that projected to the SON. 127 While it is unclear whether the CCK data suggesting a more viscerally related yet apparently specific involvement of the NTS in OT release is relevant to milk ejection, this area remains important for further study.…”
Section: Gonadal Steroids Pituitary and Hypothalamusmentioning
confidence: 99%
See 2 more Smart Citations
“…As has been shown in the previous electrophysiological studies, the mechanism is known to work in the synchronization of the neurons in the inferior olive (27,28), the suprachiasmatic nucleus (29) and the locus coeruleus (14), etc. Also, the mechanism has been considered to underlie the synchronization of oxytocin neurons in the supraoptic nucleus (30,31). It should be noted that the gap junctions provide a major means by which the neurons are coordinated in most of the interconnected networks mentioned above.…”
Section: Effects Of Electrical Coupling On the Coordinated Activity Omentioning
confidence: 99%